2018
DOI: 10.26858/cer.v0i0.7454
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan LKPD Terhadap Keterampilan Berpikir Kritis Dan Hasil Belajar Peserta Didik Kelas Xi Ipa Sma Negeri 6 Maros (Studi Materi Pokok Hidrolisis Garam)

Abstract: ABSTRAKPenelitian ini adalah penelitian eksperimen semu yang bertujuan untuk mengetahui pengaruh penggunaan LKPD terhadap keterampilan berpikir kritis dan hasil belajar kelas XI IPA SMA Negeri 6 Maros materi pokok hidrolisis garam. Desain penelitian Pretest Treatment Postest Design. Penentuan sampel dilakukan secara random kelas dan terpilih kelas XI IPA 1 sebagai kelas A dan kelas XI IPA 3 sebagai kelas B. Data dianalisis menggunakan analisis deskriptif dan uji independent sample T-Test. Hasil analisis deskri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is supported by (Ranti & Usmeldi, 2019:8), which states that the Integrated Science Student Worksheet effectively improves student competencies assessed from three competencies: attitude competence, knowledge competence, and skill competence. The same thing was also expressed by (Amalia et al, 2018) based on the results of research and discussions carried out. It can be concluded that the use of Student Worksheets affects critical thinking skills and student learning outcomes.…”
Section: Resultsmentioning
confidence: 92%
“…This is supported by (Ranti & Usmeldi, 2019:8), which states that the Integrated Science Student Worksheet effectively improves student competencies assessed from three competencies: attitude competence, knowledge competence, and skill competence. The same thing was also expressed by (Amalia et al, 2018) based on the results of research and discussions carried out. It can be concluded that the use of Student Worksheets affects critical thinking skills and student learning outcomes.…”
Section: Resultsmentioning
confidence: 92%